Peran Digital Marketing dalam Branding Lembaga Pendidikan Islam: Digital Marketing Role in Islamic Education Institutional Branding - Nurul Shafika; Syahrul Amsari (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: In the digital era, Islamic educational institutions face increasing competition requiring adaptive branding strategies through digital platforms. Specific Background: RBE Preschool Unit Al Fikih Orchard Utara Malaysia, established in 2022 and undergoing ownership transition in 2025, adopted digital marketing to communicate its institutional identity. Knowledge Gap: Previous studies largely focus on stable educational institutions, with limited attention to digital marketing in Islamic institutions experiencing ownership transition and early development phases. Aims: This study aims to analyze the role of digital marketing in building institutional branding in a transitional Islamic preschool context. Results: Using a qualitative case study with interviews, observations, and documentation, findings show that digital marketing via social media platforms such as Instagram, Facebook, and WhatsApp contributes to increased institutional visibility, formation of a professional Islamic school image, and strengthened parental trust, although challenges remain in human resource limitations and content inconsistency. Novelty: This study provides insight into digital marketing practices within Islamic educational institutions undergoing ownership transition, highlighting adaptive branding processes in a dynamic management context. Implications: The findings suggest that digital marketing serves as a strategic instrument for sustaining institutional identity and trust, while emphasizing the need for structured content planning and capacity development to ensure consistent branding outcomes. Highlights• Social media utilization supports institutional recognition among parents• Ownership transition reshapes communication and identity formation processes• Resource constraints limit continuity in content management KeywordsDigital Marketing; Islamic Education; Institutional Branding; Social Media; Ownership Transition